International Seminar on Counseling and Psychotherapy: An Islamic Perspective (American Journal of Islam and Society, 1998)
A three-day international seminar jointly organized by theDepartment of Psychology, International Islamic UniversityMalaysia (IIUM) and the International Institute of IslamicThought Malaysia (IIITM) was held August 15-17, 1997, inKuala Lumpur, Malaysia.Inaugurating the seminar, the Honomble Rector Dr. AbdulHamid A.AbuSulayman expressed happiness with the number of participants whoare trying to look at human problems from an Islamic perspective. Hesaid that intense research and hard work are needed to establish anIslamic framework of understanding human behavior and that scholarsshould not be impatient during this process. He reminded the participantsthat Muslim psychologists derive their understanding from the Qur’anand the Sunnah and that therefore their vision is different from other psychologistsand counselors. He also said that Muslim psychologists haveto delve deeply into themselves to gain self-understanding and selfstrengthbefore they can help others. The conference was marked bykeynote addresses that were delivered by renowned Muslim psychologistsfrom around the world.Dr. Malik Badri of Sudan highlighted the achievements and discoveriesof early Muslim scholars in the field of psychotherapy. He pointedout that Ibn Sina explained the learning of adaptive and maladaptivebehavior on the basis of associative learning principles. He said that IbnSina and Al-Ghazali also explicated the developments of feeling ofrevulsion toward n a h d and useful objects in terms of stimulus substitutionsimilar to today’s conditioning concept. Dr. Badri further ...